Navigating Tradition and Modernity: Sociocultural and Legal Challenges for Muslim Women in Western HRM Organizations in Pakistan - Haleema Sadia (Al Manhal Research Journal, 2025)
This study looks at the social and legal issues Muslim women face in Pakistani organizations that have taken on Western human resource management (HRM) practices. It examines how these women deal with the mix of tradition and modernity, trying to balance cultural gender roles with what’s expected in today’s workplaces. Using feminist and intersectional theories, the research looks at how religious beliefs, cultural values, and legal systems affect women’s work experiences. The study uses qualitative methods, interviewing 15 selected participants from various fields like banking, education, administration, and telecommunications to get their workplace stories. The results show notable differences based on age, job type, and personal views on Islamic teachings impacting the understanding of gender roles and women's rights to work. Participants mentioned widespread bias and discrimination, including doubts about their work skills, push back against their leadership positions, and difficulties in applying workplace harassment laws in a traditional and patriarchal setting. This study emphasizes the challenges of implementing Western HRM practices in a cultural environment that is strongly traditional. It suggests creating HR policies that are sensitive to local culture, improving legal enforcement, and running awareness programs to fight patriarchal views. By highlighting the various challenges Muslim women face, this research provides important insights for policymakers, HR experts, and researchers working to connect tradition and modernity in Pakistan's work culture.